Degradation prediction model and stem cell growth of gelatin‐PEG composite hydrogel. Issue 12 (24th August 2016) - Zhou, Nan; Liu, Chang; Lv, Shijie; Sun, Dongsheng; Qiao, Qinglong; Zhang, Rui; Liu, Yang; Xiao, Jing; Sun, Guangwei
Abstract: Gelatin hydrogel has great potential in regenerative medicine. The degradation of gelatin hydrogel is important to control the release profile of encapsulated biomolecules and regulate in vivo tissue repair process. As a plasticizer, PEG can significantly improve the mechanical property of gelatin hydrogel. However, how preparation parameters affect the degradation rate of gelatin‐PEG composite hydrogel is still not clear. In this study, the significant effect factor, glutaraldehyde (GA) concentration, was confirmed by means of Plackett‐Burman method. Then a mathematical model was built to predict the degradation rate of composite hydrogels under different preparation conditions using the response surface method (RSM), which was helpful to prepare the certain composite hydrogel with desired degradation rate. In addition, it was found that gelatin‐PEG composite hydrogel surface well supported the adhesion and growth of human mesenchymal stem cells (MSCs). Moreover, PEG concentration not only could adjust hydrogel degradation more subtly, but also might increase the cross‐linking degree and affect the cell migration. Therefore, these results would be useful to optimize the preparation of gelatin‐PEG composite hydrogel for drug delivery or tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 3149–3156, 2016.